Preaching, sermon and cultural change in the long eighteenth century - Eijnatten, Joris van (New history of the sermon, 2009)
This study examines the sermon during the 'long' eighteenth century - the era between Bossuet and Schleiermacher. it offers a broad outline of the history of preaching in this period, an overview of the research over the past three decades, and suggestions for new approaches to the subject. Thematically, the book includes chapters on such topics as the theology of the eighteenth-century sermon, preachers' instructions, the sermon in daily life, delivery as a means of reaching congregations, and audience reception of preaching. It also pays ample attention to the three important religious and intellectual currents of the long eighteenth century: (Neo-)classicism, Pietism, and the Enlightenment. - Back cover.